2002
DOI: 10.1007/s00415-002-0718-0
|View full text |Cite
|
Sign up to set email alerts
|

Balo's concentric sclerosis

Abstract: We report a case of Balo's concentric sclerosis with peculiar MRI findings. Unlike previously published cases all concentric rings in our case showed marked enhancement, supporting the view of synchronous active demyelination in the lesion. Follow-up MRI disclosed a change of the lesions into a confluent pattern more resembling a typical large MS plaque. There were no oligoclonal bands or intrathecal Ig-G synthesis. The hypothesis concerning the pathophysiology of the lesions' typical and peculiar morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…An MRI follow-up study of Baló patients has shown that the demyelinated layers form progressively in a centrifugal way [5]. More recent results nevertheless indicate that the process of active demyelination takes place synchronously rather than successively, with a progressive evolution of the lesions towards homogeneous MS plaques [6]. Furthermore, MR spectroscopic studies have confirmed the analogies between Baló's sclerosis and classical MS [7].…”
Section: Introductionmentioning
confidence: 92%
“…An MRI follow-up study of Baló patients has shown that the demyelinated layers form progressively in a centrifugal way [5]. More recent results nevertheless indicate that the process of active demyelination takes place synchronously rather than successively, with a progressive evolution of the lesions towards homogeneous MS plaques [6]. Furthermore, MR spectroscopic studies have confirmed the analogies between Baló's sclerosis and classical MS [7].…”
Section: Introductionmentioning
confidence: 92%
“…[3] Brain biopsy is the gold standard, but with the advent of MRI, many more cases are now being diagnosed ante mortem. [4] Spectroscopy (H+) shows a choline peak due to demyelination as in MS.[1] Earlier it was considered as a disease with poor prognosis, but recent cases and our case show that in a single monophasic event, complete response to therapy and survival is possible. Other presentations are the primary, progressive, and relapsing remitting type.…”
Section: Discussionmentioning
confidence: 73%
“…It has been stated that in the MR sections of the BCS lesions, the flow of the contras material may be in the peripheral direction. However, it was determined that the density of lesion layers increased in T2 weighted sections[ 7 , 21 ]. BCS lesions are frequently seen in the white matter layer (substantia alba) of cerebrum.…”
Section: Discussionmentioning
confidence: 99%
“…As supported in previously reported clinical trials, BCS is not always a fatal disease and supports the definition that it may be a self-limiting disease. Although BCS is usually known to possess a fulminant demyelinating course, there are cases in the literature with favorable prognoses and occasionally cases with spontaneous remission[ 21 ]. The unexpected finding of spontaneous remission without any treatment was noted in this case.…”
Section: Discussionmentioning
confidence: 99%